The political values and choices of husbands and wives - Kan, M; Heath, A (2006)
This article applies theoretical ideas in the literature on the household division of labor to the analysis of partners' political preferences. We regress men's and women's political party preferences on their own and their partners' characteristics using data from the 1991 British Household Panel Survey (N = 2,546). We find a symmetrical pattern of influence: Men and women both give greatest weight to their own political values but also accord some significant weight to their partners' values. Economically dependent men, however, place virtually no emphasis on their partners' political values. Apart from this, we suggest that there may be a process of mutual accommodation within couples regarding political preferences that leads to greater concordance in the partners' preferences over time.